Improving treatment and survival: a population‐based study of current outcomes after a hepatic resection in patients with metastatic colorectal cancer. Issue 11 (November 2015) - Zaydfudim, Victor M.; McMurry, Timothy L.; Harrigan, Amy M.; Friel, Charles M.; Stukenborg, George J.; Bauer, Todd W.; Adams, Reid B.; Hedrick, Traci L.
Abstract: Background: Population‐based studies historically report underutilization of a resection in patients with colorectal metastases to the liver. Recent data suggest limitations of the methods in the historical analysis. The present study examines trends in a hepatic resection and survival among Medicare recipients with hepatic metastases. Methods: Medicare recipients with incident colorectal cancer diagnosed between 1991 and 2009 were identified in the SEER(Surveillance, Epidemiology and End Results)‐Medicare dataset. Patients were stratified into historical (1991–2001) and current (2002–2009) cohorts. Analyses compared treatment, peri‐operative outcomes and survival. Results: Of 31 574 patients with metastatic colorectal cancer to the liver, 14 859 were in the current cohort treated after 2002 and 16 715 comprised the historical control group. The overall proportion treated with a hepatic resection increased significantly during the study period ( P < 0.001) with pre/post change from 6.5% pre‐2002 to 7.5% currently ( P < 0.001). Over time, haemorrhagic and infectious complications declined (both P ≤ 0.047), but 30‐day mortality was similar (3.5% versus 3.9%, P = 0.660). After adjusting for predictors of survival, the use of a hepatic resection [hazard ratio (HR) = 0.40, 95% confidence interval (CI): 0.38–0.42, P < 0.001] and treatment after 2002 (HR = 0.88, 95% CI: 0.86–0.90, P < 0.001) were associated with a reduced risk of death. Conclusions: Case identification using International Classification of Diseases, 9th Revision (ICD‐9) codes is imperfect; however, comparison of trends over time suggests an improvement in multimodality therapy and survival in patients with colorectal metastases to the liver.